The Diplomacies of Small States
XXXV, 291 p. 1 illus.
Keywords: This is an in-depth analysis of the various methods used by small states to overcome their vulnerabilities in the international arena. With its balanced approach and variety of contributions, this book is of interest to researchers and academics who focus on the developing world or multilateral diplomacy.